Cyclic Extrusion Compression Process for Achieving Ultrafine-Grained 5052 Aluminum Alloy with Eminent Strength and Wear Resistance - Jianxin Wu; Mahmoud Ebrahimi; Shokouh Attarilar; Ceren Gode; Mohammad Zadshakoyan (Metals, 2022)
Previous studies have yet to show a consistent effect of severe plastic deformation (SPD) processing on the wear behavior of different metals and alloys. To fill this scientific gap, this study investigated the effect of the cyclic extrusion compression (CEC) process, as one of the prominent SPD techniques, on the wear behavior of AA5052. In addition, the microstructure evolution and mechanical properties of the sample before and after the process were experimentally examined and studied. It was found that the yield and ultimate tensile strength of the AA5052 improved significantly after the first pass, while the elongation-to-failure decreased considerably. Further, the subsequent passes mildly changed the trend of increasing strength and reducing elongation-to-failure. SEM morphology indicated that the ductile mode of the initial annealed alloy changed to a combination of ductile and brittle failure modes, in which the level of the brittle failure mode increased with the addition of passes. TEM observations showed that the grain refinement during the CEC process included the formation of dislocation cell structures, subgrain boundaries, and low-angle grain boundaries, with the subgrain boundaries initially evolving into low-angle grain boundaries and, eventually, due to the imposition of additional plastic strain, into high-angle grain boundaries. Furthermore, the CEC process and its increased number of passes led to a significant improvement in wear resistance due to the enhanced tensile strength achieved through grain refinement. In this regard, the wear mechanism of the initial alloy was a combination of adhesion and delamination, with the plastic deformation bands changing to plowing bands with decreased adhesive wear during the process. Eventually, oxidization was found to be a mechanism contributing to wear under all conditions.